2014
DOI: 10.1016/j.jadohealth.2013.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Using Data to Improve Fidelity When Implementing Evidence-Based Programs

Abstract: In fall 2011, the South Carolina Campaign to Prevent Teen Pregnancy (SC Campaign), with funding from Office of Adolescent Health, began replicating an evidence-based curriculum, It's Your Game, Keep It Real in 12 middle schools across South Carolina. Fidelity of the curriculum was monitored by the use of lesson fidelity logs completed by curriculum facilitators and lesson observation logs submitted by independent classroom observers. These data were monitored weekly to identify possible threats to fidelity. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 14 publications
2
28
0
Order By: Relevance
“…Although each reviewed program demonstrated some behavioral change in participants, it is unclear whether these small behavioral changes are significant enough to offset the costs associated with training educators, program materials, technical assistance, and intervention development and implementation. Finally, there has been some push towards fidelity monitoring of evidence-based sexuality education programs as suggested by the U.S. Department of Health and Human Services (2012) Kershner et al, 2014). However, there remains little empirical evidence that core components of reviewed programs are consistently being implemented faithfully.…”
Section: Toward An Integrated Model Of Sexuality Educationmentioning
confidence: 99%
“…Although each reviewed program demonstrated some behavioral change in participants, it is unclear whether these small behavioral changes are significant enough to offset the costs associated with training educators, program materials, technical assistance, and intervention development and implementation. Finally, there has been some push towards fidelity monitoring of evidence-based sexuality education programs as suggested by the U.S. Department of Health and Human Services (2012) Kershner et al, 2014). However, there remains little empirical evidence that core components of reviewed programs are consistently being implemented faithfully.…”
Section: Toward An Integrated Model Of Sexuality Educationmentioning
confidence: 99%
“…The two intervention checklists were evaluated for adherence using point-bypoint agreement. The average percent of agreement (Kershener, et al, 2014) indicated structured language interventions were implemented for participants with typical development with 99% (range 94 -100%) fidelity and the multisensory with 98% (range 96 -100%) fidelity. The structured language fidelity for participants with dyslexia was 96% (range 83 -99) and the multisensory fidelity was 96% (87 -99).…”
Section: Treatment Integritymentioning
confidence: 99%
“…Fidelity has been described using five dimensions: adherence, exposure (dose), quality of delivery, participant responsiveness, and program differentiation (Dane & Schneider, 1998;Kershner et al, 2014). Adherence is the degree to which an implementation is delivered as intended by program developers (e.g., whether and to what extent a lesson is modified).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although fidelity is often discussed in the context of improving or maintaining positive program outcomes (Carroll et al, 2007;Kershner et al, 2014;Mihalic, 2004), there is also an important professional development, feedback loop, and problem-solving capacity in the monitoring process (Garbers, Flandrick, Bermudez, Meserve, & Chiasson, 2014;Kershner et al;Wiecha, Hannon, & Meyer, 2013). Using fidelity monitoring as part of a process evaluation strategy may assist "organizations reach high levels of implementation fidelity [and] … may also improve program success" (Kershner et al,p.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation